PLIS: A metabolomic response monitor to a lifestyle intervention study in older adults. Issue 11 (2nd October 2022) - Bogaards, Fatih A.; Gehrmann, Thies; Beekman, Marian; van den Akker, Erik Ben; van de Rest, Ondine; Hangelbroek, Roland W. J.; Noordam, Raymond; Mooijaart, Simon P.; de Groot, Lisette C. P. G. M.; Reinders, Marcel J. T.; Slagboom, P. Eline
Abstract: The response to lifestyle intervention studies is often heterogeneous, especially in older adults. Subtle responses that may represent a health gain for individuals are not always detected by classical health variables, stressing the need for novel biomarkers that detect intermediate changes in metabolic, inflammatory, and immunity‐related health. Here, our aim was to develop and validate a molecular multivariate biomarker maximally sensitive to the individual effect of a lifestyle intervention; the Personalized Lifestyle Intervention Status (PLIS). We used 1 H‐NMR fasting blood metabolite measurements from before and after the 13‐week combined physical and nutritional Growing Old TOgether (GOTO) lifestyle intervention study in combination with a fivefold cross‐validation and a bootstrapping method to train a separate PLIS score for men and women. The PLIS scores consisted of 14 and four metabolites for females and males, respectively. Performance of the PLIS score in tracking health gain was illustrated by association of the sex‐specific PLIS scores with several classical metabolic health markers, such as BMI, trunk fat%, fasting HDL cholesterol, and fasting insulin, the primary outcome of the GOTO study. We also showed that the baseline PLIS score indicated which participants respond positively to the intervention. Finally, we explored PLIS in an independent physical activity lifestyle intervention study, showing similar, albeit remarkably weaker, associations of PLIS with classical metabolic health markers. To conclude, we found that the sex‐specific PLIS score was able to track the individual short‐term metabolic health gain of the GOTO lifestyle intervention study. The methodology used to train the PLIS score potentially provides a useful instrument to track personal responses and predict the participant's health benefit in lifestyle interventions similar to the GOTO study.